Kajian Kapasitas Sambungan Tubular Chord Ganda Digrout Dengan Analisis Elemen Hingga - Made Suarjana; Bayu Purnama A. Malida (Jurnal Teknik Sipil, 2020)
AbstractThe type of offshore platform for oil and natural gas exploration that is widely used in Indonesia is steel jacket platform. Jacket type platforms are generally made of tubular steel. During the service life, jacket type platforms often suffer damage to the joints. One preferred repair method for platform structure elements is by grouting. In the API RP 2A WSD NORSOK N-004 regulations, the formulations of tubular joint capacity reinforced by grouting are specified. The formulations in the regulations are empirical equations that need to be examined experimentally in the lab or tested by finite element analysis method. In this study, testing using the finite element method is conducted. The discussion is limited to the type of tubular joint with double skin chord. By finite element analysis, the influence of grout thickness, grout strength, inner chord thickness, and outer chord thickness to capacity of tubular joints reinforced with grout is investigated. From the analysis, it was found that the thickness and strength of the grout do not have a significant effect on increasing tubular joint capacity. While the thickness of both the inner and outer chords have a significant effect on increasing the tubular joint capacity. By comparison, the results of finite element method analysis are quite close to the results based on API regulation and in general the API results are more conservative except for cases with out-of-plane bending load.AbstrakTipe anjungan lepas pantai untuk eksplorasi minyak dan gas alam yang banyak dipakai di lepas pantai Indonesia adalah tipe jaket baja. Anjungan tipe jaket umumnya dibuat dari baja tubular. Dalam masa layannya, anjungan tipe jaket sering mengalami kerusakan pada sambungan (joint). Salah satu metode perbaikan yang disukai untuk elemen struktur anjungan adalah dengan di-grout. Dalam peraturan API RP 2A WSD dan NORSOK N-004 telah diberikan formulasi perhitungan kapasitas sambungan tubular yang diperkuat grout. Formulasi pada peraturan-peraturan ini merupakan persamaan-persamaan empiris yang perlu diperiksa dengan eksperimental di lab atau diuji dengan analisis metode elemen hingga. Pada penelitian ini dilakukan pengujian dengan metode elemen hingga. Pembahasan dibatasi pada tipe sambungan tubular dengan batang utama (chord)  ganda. Dengan analisis elemen hingga akan dilihat pengaruh tebal grout, kuat grout, tebal chord dalam, dan tebal chord luar terhadap kapasitas sambungan tubular yang diperkuat di-grout. Dari hasil analisis diperoleh bahwa tebal dan kuat grout tidak memberikan pengaruh yang signifikan terhadap peningkatan kapasitas sambungan tubular (tubular joint). Sedangkan tebal chord dalam dan luar keduanya memberikan pengaruh yang signifikan terhadap peningkatan kapasitas sambungan tubular. Dari perbandingan diperoleh hasil-hasil analisis metode elemen hingga cukup mendekati  hasil-hasil berdasarkan peraturan API RP 2A WSD dan hasil persamaan API RP 2A WSD umumnya ada pada sisi konservatif kecuali pada kasus beban momen keluar bidang.